2019
DOI: 10.1111/scs.12801
|View full text |Cite
|
Sign up to set email alerts
|

The association of frailty with oral cleaning habits and oral hygiene among elderly home care clients

Abstract: The association of frailty with oral cleaning habits and oral hygiene among elderly home care clients Background: Increasing numbers of frail elderly people living at home but dependent on supportive care will face complex oral health challenges. Objectives: To investigate the associations of frailty status with oral cleaning habits and oral hygiene taking into account the effects of preventive oral health intervention among home care clients aged 75 or over. Methods: Data were gathered by interviews and clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
48
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(51 citation statements)
references
References 49 publications
2
48
1
Order By: Relevance
“…After initial screening of 835 titles and abstracts, 70 articles were selected for full-text review, 26 of which were included in qualitative synthesis of this review (Figure 1). Seventeen of the studies were cross-sectional [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] (Table 1), and nine were longitudinal [41][42][43][44][45][46][47][48][49] (Table 2). Despite being the innovative focus of this review, none of the studies encountered were translational in nature by either engaging a dentist in administering frailty assessment or utilising frailty status for dental treatment planning or gauging prognosis for oral health outcomes.…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…After initial screening of 835 titles and abstracts, 70 articles were selected for full-text review, 26 of which were included in qualitative synthesis of this review (Figure 1). Seventeen of the studies were cross-sectional [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] (Table 1), and nine were longitudinal [41][42][43][44][45][46][47][48][49] (Table 2). Despite being the innovative focus of this review, none of the studies encountered were translational in nature by either engaging a dentist in administering frailty assessment or utilising frailty status for dental treatment planning or gauging prognosis for oral health outcomes.…”
Section: Study Selectionmentioning
confidence: 99%
“…50),36 and the presence of three or more dry mouth symptoms at baseline was positively associated with being frail after three years (OR = 2.03) 49. Higher self-reported frequency of tooth brushing (OR = 0.40) and denture cleaning (OR = 0.30) were negatively associated with being frail 45. 4 | D ISCUSS I ONConsistent with the findings of previous cross-sectional2 and longitudinal 3 systematic reviews, this review demonstrated both cross-sectional and longitudinal associations between oral health F I G U R E 2 Fish bone diagram demonstrating factors that are considered by oral healthcare professionals during treatment planning and influence the treatment that is rendered characteristics and frailty status.…”
mentioning
confidence: 97%
“…30 Previous studies have focused on the clinical aspect regarding the oral health of home-dwelling older people, with fewer studies examining the perceived or oral health behaviour of domiciliary care clients. [30][31][32] More knowledge is needed on perceived oral health and the oral health behaviours of home-dwelling older people with and without domiciliary care. This study aimed to compare the perceived oral health and oral health behaviours of home-dwelling older people who receive domiciliary care and those who do not use data from two national cross-sectional surveys in 2000 and 2011.…”
mentioning
confidence: 99%
“…In the present study, the rural elderly respondents reported brushing their teeth on average 1.99 times a day; the frequency of tooth cleaning differed significantly between the nonfrail and frail groups and can be a predictor of PF. Frail elderly people require guidance and support regarding oral cleaning habits, which can benefit oral health, and oral health should be included in the daily care plan of home care for elderly people [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Frail elderly people tend to have poorer oral hygiene than their nonfrail counterparts [ 11 ]. A study of elderly people in Mexico revealed that, for every additional intact tooth, the probability of frailty decreased by 5% [ 12 ].…”
Section: Introductionmentioning
confidence: 99%